DEVELOPMENT OF ANALYSIS METHOD FOR IODATE SPECIES BASED ON FLOW INJECTION ANALYSIS - HENRY DULANLEBIT (NIM: 20507089), YEANCHON
Iodine is an element nonmetal and essential micronutrient needed by human body in a trace amount. Iodine deficiency may cause brain damage, mental retardation, cretinism and endemic goiter. Besides as diet supplement, iodine is also added into medicines as antiseptic and multivitamin. Existence of iodine in nature is found in form of compounds, among others as potassium iodide and potassium iodate. Potassium iodate is a stabile compound and cannot easily be damaged, while potassium iodide is not stabile particularly for long storage. It is this stability of potassium iodate that is recommended to prevent iodine deficiency in some tropical states. Analysis method of detecting iodine has widely been used, where iodometric analysis is a standard method to determine iodine content. The application of spectrophotometric method to determine iodate in 350 nm absorbing area has also been developed. Besides from iodometry and spectrophotometry, some analysis methods have also been used in determining iodate, among others : electrochemistry, gas chromatography-mass spectrometry, ion chromatography, and x-ray fluorescence. These methods have been successfully applied to determine iodate in salt sample, fresh water, and sea water. However, due to low sensitivity of these methods and difficulty if ion separation in certain matrix concentrations, it needs development of other method in determining iodate. Flow Injection Analysis (FIA) method has been developed for determining iodate under acid condition by using red pirogalol. This method is successfully applied to water sample. The development of flow injection-based spectrophotometry method has also been conducted. This method is based on blue complex between triiodide ion and starch. The development of FIA-based spectrophotometry method for determining iodine in urine sample has been conducted as well. Where, sample dilution conducted produced no different results from that without dilution. Flow injection analysis methods can be used to an analysis of high salt containing waters. Where, this method is very selective and with no influence of matrix. Flow injection method is simpler, easy to use, needs a small quantity of sample volume, and more rapid compared to manual methods. The time taken for analysis is short with a high sampling frequency. In addition, this method can be modified with different concentration ranges or by changing sample injection volume.